Consistency Testing of Light Weight Deflectometer (LWD) Tool Pusjatan on Composite Road (Case Study of Road Section Soreang New Ring Road, Bandung Regency) - Bahy, Fransiskus Roystone; Kaok, Kasius Kaok; Syafier, Siegfried; Fadhila, Raisa (Universitas Negeri Padang, 2024)
In an era of rapid technological and infrastructural development, the quality of roads is critical to ensuring efficient and safe mobility. Composite roads, which consist of a mixture of different types of construction materials, have become an attractive option in road development in various regions. However, to ensure the success of composite roads, structural consistency and performance must be considered. A Light Weight Deflectometer (LWD) is a device used to measure the instability of road layers by applying surface pressure and measuring the resulting deflection. Although the use of LWD is common in the road construction industry, specific research on LWD consistency testing of composite roads is limited. This study investigates and analyzes the consistency of LWD on composite roads to improve the understanding of its performance. The results of the study on composite pavements conducted at three points with 30 trials showed a coefficient of variance of less than 5%. This result indicates very strong data consistency. Based on these consistency values, the LWD is acceptable, but it needs to be correlated with other tools to determine its validity. If the consistency and correlation meet the requirements or are less than 5%, LWD has a good chance of being used in composite pavements.